(untitled) (Fiep Bulletin - online, 2016)
Objective: To identify the experience and expertise of nurses in the performance of the nasogastric and nasoenteral probe placement procedure. Method: A quantitative study , carried out with 30 nurses of a public hospital in the municipality o Patos – PB, Brazil. Between the months of August and September 2011, by means of interviews. Results: The majority of the professionals interviewed performed the procedure, still during the undergraduate studies, opted for sterile gloves instead of procedure gloves, used appropriate lubricant; hygenised the probe and washed hands before and after the feeding; denied difficulties and doubts about the procedure. Conclusion: The results were satisfactory in this study, however, it is considered necessary the discussion of nursing techniques , specifically about the passing of nasogastric and nasoenteral probes, in scientific studies, seen as these contribute to the improvement of the developed actions.